Renal cell carcinoma - Hsieh, James J. (Nat Rev Dis Primers, 2017)
Renal cell carcinoma (RCC) denotes cancer originated from renal epithelium and accounts for >90% of cancers in the kidney. The disease encompasses >10 histological and molecular subtypes, of which clear cell RCC (ccRCC) is most common and accounts for most cancer-related deaths. Although somatic VHL mutations have been described for some time, more-recent cancer genomic studies have identified mutations in epigenetics regulatory genes and demonstrated marked intratumour heterogeneity, which could have prognostic, predictive and therapeutic relevance. Localized RCC can be successfully managed with surgery whereas metastatic RCC is refractory to conventional chemotherapy. However, over the past decade, marked advances in treatment of metastatic RCC have been made, with targeted agents including sorafenib, sunitinib, bevacizumab, pazopanib and axitini that inhibit vascular endothelial growth factor (VEGF) and its receptor(VEGFR) and everolimus and temsirolimus, which inhibit mTOR complex 1, being approved. Since 2015, agents with additional targets aside from VEGFR have been approved, such as cabozantinib and lenvatinib; immunotherapies such as nivolumab have also been added to the armamentarium for metastatic RCC. Here, we provide an overview of the molecular biology of RCC, with a focus on ccRCC, as well as updates to complement current clinical guidelines and an outline of potential future directions for RCC research and therapy.